Simulation Study of Environmentally Friendly Lead-Free All-Perovskite Tandem Solar Cells - Luo, Wei; Hua, Yan; Han, Jian (Scientific Journal of Technology, 2026)
The toxicity of lead in perovskite solar cells has long been a significant barrier to their widespread commercialization. The improvement of environmentally friendly tandem solar cells presents the additional challenge of identifying highly efficient materials for both the wide-bandgap top cell and the narrow-bandgap bottom cell. In this study, we have reported a lead-free, non-toxic tandem perovskite solar cell , investigated through numerical simulations, by pairing an Sb³⁺-doped double perovskite, Cs2AgBi0.75Sb0.25Br6, with a bandgap of 1.8 eV, as the top cell, with a tin-based MASnI₃ bottom cell, which has a bandgap of 1.3 eV. Upon optimization, the simulated device achieves an open-circuit voltage of 2.29 V, a current density of 15.5 mA/cm², and a remarkable photovoltaic conversion efficiency of 26.8%. These results are on par with the performance of state-of-the-art Pb-based tandems, highlighting the competitiveness of Pb-free materials. These simulation results highlight the potential of lead-free perovskite tandem architectures for environmentally sustainable, high-efficiency photovoltaic applications.